Vida Saludable: Etiquetas de suplementos dietéticos - Karla P. Shelnutt (EDIS)
This revised 1-page handout is the Spanish-language version of FCS8854/FY1035: Healthy Living: Dietary Supplement Labels Word Search. It was written by Karla P. Shelnutt and published by the UF Department of Family, Youth and Community Sciences, September 2011.